The prohibition of alienation of ecclesiastical charitable institutions` property in Roman Empire - KOWALCZYK, EWARYST (Prawo Kanoniczne, 2012)
The subject of the submission are the prohibitions of alienations of Christian charitable institutions` estates. Christian charitable institutions came into being in 4th Century. The charitable institutions displayed a new way of charitable activity to advantage. The charitable institutions became the matter of ecclesiastical legal regulation in 5th Century. Some of those regulations concerned interdictions of sale, donations, lend, lease or any disposal of Church and its institutions` property. The prohibition of alienation indicated that the imperial legislation was focused on well existence and functioning of ecclesiastical charitable institutions. The aim of imperial legislation was the protection of ecclesiastical property from diminution by the acts of fraud conducted by dishonest clergy or contracting party. According to Roman legal tradition the owner was permitted to alienate his property. But by the cause of public benefit ecclesiastical and imperial authorities enforced limitation of this owner`s right. Now, we can say, that the existing and activity of charitable institutions was a sphere of privet and public interests.